The relationship between motivation and retention in the homestay business in Ella - Sumithra, N.K. (University of Jaffna, 2020)
The homestay concept creates a unique experience for the guests. It also empowers homestay operators to get additional income and create job opportunities. Ella is a popular destination for homestay tourism in Sri Lanka. This study is conducted to find Socio-cultural, Economic and Environmental Motivations for homestay operators in Ella -Sri Lanka. The researcher used the quantitative method. This study is based on primary and secondary data. Primary data was collected through five point Likert scale questionnaires and 80 homestay operators were selected for questionnaire data collection. The researcher used simple A simple random sampling technique. According to findings, there is a strong positive relationship between Economic Motives and Motivation to retain business and a strong positive relationship between Social Motives and Motivation to retain business. However, there is a weak positive relationship between Environmental Motives and Motivation to retain business. Homestay is a potentially easy solution for the demand for accommodation facilities for tourism. Policymakers can expand the homestay concept into developing small-medium enterprises (SME sector) in the tourism industry in Sri Lanka. As well the government can facilitate to encourage growing numbers of homestay entrepreneurs.
Keywords: Economic motives; Environmental motives; Homestay and social motives